Financial security of the state - Reznik, O. M.; Рєзнік, О. М.; Hetmanets, O. P.; Гетманець, О. П.; Kovalchuk, A.; Nastyuk, V.; Andriichenko, N.; Гетманець Ольга Петрівна (Journal of Security and Sustainability Issues. – 2020. – Vol. 9, № 3. – P. 843-852, 2020)
Стаття присвячена дослідженню фінансової безпеки держави як складової його національної безпеки. Встановлено, що фінансова безпека - це здатність держави адекватно і негайно реагувати на внутрішні і зовнішні негативні фінансові впливи в мирний час і в надзвичайних ситуаціях, зокрема в контексті гібридної війни.

The article deals with the study of the fnancial security of the state as a component of its national security. It has been established that fnancial security is state’s ability to react in an adequate and immediate way to internal and external negative fnancial inﬂuences in peacetime and in emergency situations, in particular in the context of a hybrid war. It has been established that the components of the fnancial security of the state are banking, debt, budget, currency and monetary security. It has been found out that corruption, fnancial and economic crime, hybrid war, fscal decentralization, and lack of a strategy to protect the fnancial and economic interests of the state are threats to the fnancial security of the states in the present conditions. At the same time, proper protection of the fnancial security of the state against internal and external threats is possible only in case of quality management of the fnancial and economic sphere, frst of all, this is the identifcation of threats to the fnancial security of the state, conducting of fnancial control, and counteraction and combating against fnancial and economic crimes, which is the task of law enforcement agencies. The development of the idea of creating a single law enforcement agency of Ukraine empowered to prevent, detect, suspend and investigate fnancial and economic crimes was considered. For comparison, attention was drawn to foreign experience, namely Italy, Romania, Macedonia, Austria, Croatia, Latvia, Lithuania, for which the activity of such law enforcement agencies is already established practice. The positive aspects which can be implemented in Ukraine as well as in other countries, intending to create a new law enforcement entity, were emphasized.

Статья посвящена исследованию финансовой безопасности государства как составляющей его национальной безопасности. Установлено, что финансовая безопасность - это способность государства адекватно и незамедлительно реагировать на внутренние и внешние негативные финансовые влияния в мирное время и в чрезвычайных ситуациях, в частности в контексте гибридной войны.
Keywords: Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u Scopus; Україна. Ukraine. Украина; Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; financial system; financial security; national security; corruption; organized crime; financial police; фінансова система; фінансове забезпечення; національна безпека; корупція; організована злочинність; фінансова поліція; поліція; полиция; police; финансовая система; финансовая безопасность; национальная безопасность; коррупция; организованная преступность; финансовая полиция; гібридна війна